Dynamics of non-spherical dust in the coma of 67P/Churyumov– Gerasimenko constrained by GIADA and ROSINA data. (23rd November 2017) - Ivanovski, Stavro L; Della Corte, V; Rotundi, A; Fulle, M; Fougere, N; Bieler, A; Rubin, M; Ivanovska, S; Liuzzi, V
Abstract: Among the comet 67P/Churyumov–Gerasimenko (67P/C-G) in situ measurements, the closest that have ever been performed at a comet nucleus, are also those of speed, mass, and cross-section of cometary grains performed by the Grain Impact Analyser and Dust Accumulator (GIADA) instrument. To interpret GIADA data, we performed dust dynamical numerical simulations with both spherical and non-spherical (spheroids) shapes. This allowed us to analyse how the grain non-sphericity affects the data interpretation. We find that some measured dust speeds are unlikely reproducible when a spherical shape is considered. We considered two GIADA observational periods, 2015 February 19–27 and 2015 March 13–28. Gas parameters calibrated with the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA) measurements have been used to retrieve the gas conditions to set up the dust particle motion. The dust grains are assumed to be out of the near nucleus coma, i.e. where the gas velocity is radial and constant, therefore they are either aligned or have random but constant orientation with respect to the gas drag. We reproduced the GIADA dust speeds, using spheres and two different spheroidal shapes. We find that the particle shapes that reproduce best the GIADA dust speeds are consistent with the particle shape constrained by the GIADA data. We obtain different terminal velocities for spherical and non-spherical particles of the same mass. The shape, which reproduces the GIADA data, is oblate rather than prolate spheroid. We obtain rotational frequencies of the spheroidal particles that best fit the GIADA measurements in these periods.